Measuring financial stress – A country specific stress index for Finland - Jarkko Huotari (Bank of Finland, 2015)
​I propose a financial stress index (FSI) for the Finnish financial system that aims to reflect the functionality of the financial system and provide an aggregate measure of financial stress in the money, bond, equity and foreign exchange markets and the banking sector. The FSI is a composite index that combines information from these markets and provides a measure of stress in the financial system as a whole. The FSI has obvious benefits for all participants in the financial markets who need a tool for monitoring the functioning of the financial markets, as it provides information on systemic stress events which are not as easily captured with the stress measures of individual markets or sectors. The ESRB recommendation (ESRB, 2014a) also states that national or international FSIs could be used when making a decision about the release of the counter-cyclical capital buffer. Hence, the index can also be used to support the macro-prudential policy decision making in Finland.
URN:NBN:fi:bof-201503171116
Keywords: G01; G28; C43; 330